Мамилов Н.Ш., Муталипов Р.А., Сутуева Л.Р., Конысбаев Т.Г. Морфологическое разнообразие сазана Cyprinus carpio в западной части озера Балкаш и Капшагайском водохранилище: Казахский национальный университет имени аль-Фараби, Казахстан, г. Алматы (Eurasian Journal of Ecology, 2018)
Negative human impact on freshwater ecosystems lead to decreasing of diversity and fall down offish catches around the world. Fishes are one of the biological indicators of state of aquatic ecosystems.And so, carp Cyprinus carpio from the Balkhash watershed was chosen for the investigation in respect tohigh level of human impact and big commercial importance of the fish here. Investigation of variabilityof external morphology of carp from the western part of the Balkhash Lake and the Kapshagay waterreservoir had been done. Existence of external morphological abnormalities (malformations), fluctuating asymmetry of bilateral characteristics, variability of 30 morphometric and 12 meristic measures aswell as distribution of pores of the head lateral line. Principal components analysis was applied to intrapopulation variability assessment. Many of the investigated fishes were in well condition, but individual variability for both water bodies became larger then it was before strong human impact. Developmentalhomeostasis was disturbed in the both water bodies. The carp was presented generally with similarmorphological forms in the western part of the Balkhash Lake and Kapshagay water reservoir samplesof carps with a few specific forms. Big percent of external malformations was revealed in the sample ofcarp from the western part of the Balkhash Lake. That could be a result of lack of adaptation ability inconditions of strong negative human impact in this part of the lake.Key words: ichthyomonitoring, variability, carp, Balkhash basin, homeostasis